1996
DOI: 10.1038/nm1196-1225
|View full text |Cite
|
Sign up to set email alerts
|

Increased mu opioid receptor binding detected by PET in cocaine–dependent men is associated with cocaine craving

Abstract: The endogenous opioid system has been recently implicated in the reinforcing actions of cocaine and other addictive drugs. In this study we examined mu opioid receptor binding in ten cocaine-dependent men and seven nonaddicted controls using positron emission tomography and [11C] carfentanil. Mu opioid binding was increased in several brain regions of the cocaine addicts studied 1-4 days after their last use of cocaine. Binding was positively correlated with the severity of cocaine craving experienced at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
1
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(157 citation statements)
references
References 29 publications
9
141
1
4
Order By: Relevance
“…In fact, we have reported that rats maintained on high-dose methadone maintenance show no cocaine-place preference and no cocaine-induced up-regulation of mu-opioid receptor mRNA in the nucleus accumbens core (Leri et al, 2006). This is notable because the effect of cocaine exposure on mu-opioid receptor density and function in mesocorticolimbic areas (Azaryan et al, 1996;Unterwald et al, 1992;Unterwald, 2001;Yuferov et al, 1999) has been associated to the intensity of cocaine cravings in humans (Gorelick et al, 2005;Zubieta et al, 1996), and to a variety of behavioral, electrophysiological and neurochemical responses to cocaine in animals (Mathon et al, 2005a(Mathon et al, , b, 2006Tang et al, 2005;Hummel et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, we have reported that rats maintained on high-dose methadone maintenance show no cocaine-place preference and no cocaine-induced up-regulation of mu-opioid receptor mRNA in the nucleus accumbens core (Leri et al, 2006). This is notable because the effect of cocaine exposure on mu-opioid receptor density and function in mesocorticolimbic areas (Azaryan et al, 1996;Unterwald et al, 1992;Unterwald, 2001;Yuferov et al, 1999) has been associated to the intensity of cocaine cravings in humans (Gorelick et al, 2005;Zubieta et al, 1996), and to a variety of behavioral, electrophysiological and neurochemical responses to cocaine in animals (Mathon et al, 2005a(Mathon et al, , b, 2006Tang et al, 2005;Hummel et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In humans, mu-opioid receptor binding detected by positron emission tomography (PET) using 11 C-carfentanil, has been demonstrated to be increased in several brain regions of cocaine addicts, after 1-4 days of abstinence (Zubieta et al 1996), and kappa-opioid receptor density measured autoradiographically has been demonstrated to be increased in brain tissue of cocaine overdose victims (Mash and Staley 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in OR binding have been associated with craving scores in cocaine-dependent volunteers undergoing cocaine withdrawal (Zubieta et al 1996). In a larger sample, it would be of interest to evaluate the relationship between OR binding potential in these regions and measures of withdrawal or craving for opiates.…”
Section: Discussionmentioning
confidence: 99%